Odpowiedź :
Odpowiedź:
[tex]Zad1.\\a) 2x+7=11\\2*3+7=11\\6+7=11\\13\neq 11\\b) x^{2} -1+x=1\\1^{2} -1+1 =1\\1-1+1=1\\0+1=1\\1=1\\c) \frac{20}{x+1}=5 \\\frac{20}{4+1}=5\\\frac{20}{5}=5\\4\neq 5\\d) 5*(x-4)-x=8\\5*(7-4)-7=8\\5*3-7=8\\15-7=8\\8=8\\e)6+x=10\\6+4=10\\10=10\\f)(x+6)/2=10\\(12+6)/2=10\\18/2=10\\9\neq 10\\B.a) 20+-8*x=5\\ 20+9-8*3=5\\20+9-24=5\\5=5\ dla x=3\\20+25-40=5\\5=5 \dla\ x=5\\20+1-8=5\\13\neq 5\ dla\ x=1\\b) (x-5)*(x+5)= (x^{2} -25) = 66\\1-25 = 66\\-24\neq 66\\36-25 =66 \\[/tex][tex]11\neq 66 \ dla x=6\\225-25 = 66\\200\neq 66 \ dla\ x=15\\c)\frac{15}{x+1} = 3\\ \frac{15}{0+1} =3\\15/1=3\\15\neq 3\ dla\ x=0\\\frac{15}{2+1} = 3\\15/3 = 3\\5\neq 3 \ dla x=2\\\frac{15}{4+1} = 3\\15/5 = 3\\3 = 3 \dla \x=4\\ d) (-5+5)*(-5-4)=0\\0*(-9)=0\\0=0 \ dla\ x=-5\\(5+5)*(5-4)=0\\10*1=0\\10\neq 0 \ dla\ x=5\\9*0 = 0\\0 = 0\ dla\ x=4\\f) 16 = 16 \ dla\ m=4\\64 = 16 dla \ m=8\\(-4)^{2} = 16\\16 = 16 \ dla\ x=-4\\f) 1+12-3*1 = 10\\13-3 = 10\\10 = 10 \ dla x=1\\[/tex][tex]6+12-3*2 = 10\\18-6 = 10\\12\neq 10\ dla x=3\\[/tex][tex]C. a) 2*3 = 3+5\\6 \neq 8\ nie\\\\b) 9-4 = 3 +2\\5=5\ tak\\ c) 5*(3+3)=3*10\\5*6=30\\30=30\ tak\\d)7-3 = 12/(3+1)\\4 = 12/4\\4\neq 3\ nie\\e) 24-4*3 =12/3\\24-12 = 4\\12\neq 4\ nie\\f)6+5*3=10-3\\6+15=7\\21 \neq 7\ nie[/tex]
Szczegółowe wyjaśnienie: